2021
DOI: 10.3389/fnut.2021.654624
|View full text |Cite
|
Sign up to set email alerts
|

Nano-encapsulated Iron and Folic Acid-Fortified Functional Yogurt Enhance Anemia in Albino Rats

Abstract: Iron deficiency anemia (IDA) is a major health concern in developing countries, and these see an increased incidence in pregnant women and children in particular. The contribution of dairy products as natural products in drug delivery approaches is inspiring. This study aimed to analyze the application of iron (Fe) and folic acid (FA) bovine serum albumin-nanoparticles (BSA-NPs) as anti-anemic pharmacological agents that fortify stirred functional yogurt (SFY), comparing these with a plain control and SFY fort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 70 publications
2
21
0
Order By: Relevance
“…The sensory evaluation of cultured milk beverages and probiotic yoghurt fresh samples were assessed by 20 consumer-oriented panellists (8 men and 12 women, 27 to 51 years) at Food Science Department, Faculty of Agriculture, Alexandria University, Egypt according to [ 31 33 ]. The criteria for selection depended on their experience and background related to fermented dairy products.…”
Section: Methodsmentioning
confidence: 99%
“…The sensory evaluation of cultured milk beverages and probiotic yoghurt fresh samples were assessed by 20 consumer-oriented panellists (8 men and 12 women, 27 to 51 years) at Food Science Department, Faculty of Agriculture, Alexandria University, Egypt according to [ 31 33 ]. The criteria for selection depended on their experience and background related to fermented dairy products.…”
Section: Methodsmentioning
confidence: 99%
“…El-Hendy et al (2001) reported Zn deficiency have adverse effect to growth rate, specific organ weight, haematology parameter, Zn, Cu, and Fe serum level in rat. Further description by Darwish et al (2021) that level of Zinc was related to the absorbance of iron in blood cells. In food, Zinc is highly contained in oyster (Kaur et al 2014).…”
Section: Complete Blood Test Description Post Treatmentmentioning
confidence: 99%
“…The so-called "bioactive peptides" (BAPs) are interesting from nutrition and healthcare perspectives (10). Probiotic bacteria were reported to enhance iron absorption and utilization because of bioactive factors of fermented milk; hence they enhance and protect from iron-deficiency anemia (32)(33)(34). On the other hand, whey protein-derived bioactive peptides were reported to show considerable capacity for binding properties for cations, such as calcium, iron, and zinc (35), and the potential to regulate the intestinal microbiota that encourages mineral absorption by the digestive tract (8), which can explain the significant increase of Hb of G1 and G2 who ate the PRO-WPI products compared to placebo.…”
Section: Effect On Anthropometric Measurements and Hematology Parametersmentioning
confidence: 99%